Template Assembled Large‐Size CsPbBr3 Nanocomposite Films toward Flexible, Stable, and High‐Performance X‐Ray Scintillators - Wang, Baiqian; Peng, Jiali; Yang, Xin; Cai, Wensi; Xiao, Hongbin; Zhao, Shuangyi; Lin, Qianqian; Zang, Zhigang (Laser & photonics reviews, 2022)
Metal halide perovskite‐based high‐performance X‐ray scintillator is considered as one of the most favorable candidates applied in the fields of medicine, industry, and science. However, the current X‐ray scilltillators based on perovskites still suffer from the issue of poor stability, which impedes their further wide applications. Herein, a template assembled method to prepare large‐size, flexible, and stable CsPbBr3@Polymethyl methacrylate composite films in ambient conditions is developed and their detection performance is studied. The composite films can maintain 94% and 81% of the initial PL intensity after 2000 cycles bending and storing in water over 2520 h, respectively. In addition, the prepared scintillators exhibit not only a low detection limit of 40.1 nGyair s−1 and a high spatial resolution of 8.0 lp mm−1, but also an excellent tolerance against radiation (108 h). Thus, this simple but yet effective method would not doubt pave the way for further development of scintillators and might be well applicable to other metal halides. X‐ray flexible scintillators of perovksites have emerged as one of the most favorable candidates in medical radiography, security inspection, nuclear radiation monitoring, and space exploration. Coating perovskite nanocrystals with polymer is an effective strategy to improve their stability and reduce heavy metal leakage. Herein, the flexible scintillators of CsPbBr3@Polymethyl methacrylate films exhibit low detection limit and high spatial resolution.